A novel method for the evaluation and certification of false start apparatus in sprint running - Willwacher, S.; Feldker, M.-K.; Zohren, S.; Herrmann, V.; Brüggemann, G. P. (Procedia Engineering, 2013)
The purpose of the present study was to develop a methodology for performance assessment of false start detection devices. Therefore, a four step project was initiated to develop a testing protocol which can be used for the evaluation and certification of these devices. A database of push-off force characteristics of athletes from a wide range of performance levels was created by analyzing 438 starting performances of 101 athletes, including the currently two fastest men in the world. A custom-made 3D force start block was developed for this purpose to precisely analyze the forces applied to the front and the rear block of the starting device. From the database, four force patterns were identified using cluster analysis techniques. Subsequently, a pneumatically driven machine was developed, that is capable to reproduce these force patterns with a low measurement error and high repeatability. Initial testing of false start apparatus highlights the need for further improvements of the systems, but also the need for further methodological improvements, especially with respect to the criterion that is used to detect the reaction time from a given sensor waveform.